2011
DOI: 10.1093/rpd/ncr194
|View full text |Cite
|
Sign up to set email alerts
|

Calculated organ equivalent doses for individuals in a sitting posture above a contaminated ground and a PET imaging room

Abstract: In this paper, phantoms representing sitting postures were developed and implemented in the MCNPX code to perform dose calculations. For the ground contamination case, isotropic planar source of 137 Cs was used. The male sitting phantom received an effective dose rate of 37.73 nSv h 21 for a contamination of 30 kBq m 22 . The gonadal equivalent dose of the male sitting phantom was 40 % larger than that from the standing phantom. For the positron emission tomography clinic, a point photon source with the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…The Adult Male and Adult Female phantoms from RPI were also expanded into phantoms of specific weights, representing the 5 th , 25 th , 50 th , 75 th , and 95 th weight percentiles, female phantoms with different breast sizes to study the effect on the lung counting of internally deposited radionuclides [29], and 10 phantoms representing overweight and obese individuals with body mass index (BMI) from 26 to 48 kg/m 2 [115]. A unique type of posture-specific phantom was also reported by this group to more realistically model how people behave in real-world radiation environments, including a pair of walking phantoms [116], sitting phantoms [117], and computational human for animated dosimetry (CHAD) phantoms with adjustable postures defined by a motion capture system for critical accidents [118]. Fig.…”
Section: ) Brep Phantoms (From the 2000s To Present)mentioning
confidence: 99%
“…The Adult Male and Adult Female phantoms from RPI were also expanded into phantoms of specific weights, representing the 5 th , 25 th , 50 th , 75 th , and 95 th weight percentiles, female phantoms with different breast sizes to study the effect on the lung counting of internally deposited radionuclides [29], and 10 phantoms representing overweight and obese individuals with body mass index (BMI) from 26 to 48 kg/m 2 [115]. A unique type of posture-specific phantom was also reported by this group to more realistically model how people behave in real-world radiation environments, including a pair of walking phantoms [116], sitting phantoms [117], and computational human for animated dosimetry (CHAD) phantoms with adjustable postures defined by a motion capture system for critical accidents [118]. Fig.…”
Section: ) Brep Phantoms (From the 2000s To Present)mentioning
confidence: 99%
“… 20 , 66 Han et al 67 developed walking phantoms suitable for radiation dosimetry in external photon exposure scenarios. Another study by Su et al 68 reported on sitting phantoms designed for internal radiation dosimetry studies. Recently, mesh-type ICRP phantoms were deformed to multiple non-standing postures using a posture-change method based on a rigid shape-deformation algorithm and motion-capture technology 69 to measure the radiation dose in specific situations.…”
Section: Extensions Of Reference Phantomsmentioning
confidence: 99%
“…20,66 Han et al 67 developed walking phantoms suitable for radiation dosimetry in external photon exposure scenarios. Another study by Su et al 68 reported on sitting phantoms designed for internal radiation dosimetry studies. The evolution of computational phantoms from simple macro-bodies to detailed personalized models.…”
Section: Motion and Posture Simulationmentioning
confidence: 99%
“…Several authors have calculated fluence-to-dose conversion coefficients for protons using stylized (mathematical and voxel) phantoms in the standing posture (2)(3)(4)(5) . There are few studies in the literature that attempt to calculate doses in computational phantom in the sitting posture, but even in these studies only photon, electron or positron doses were calculated (6)(7)(8)(9)(10)(11) . In a previous paper, organ dose conversion coefficients for protons were calculated using the sitting and standing female hybrid phantom and the influence of the posture in absorbed dose was discussed (12) .…”
Section: Introductionmentioning
confidence: 99%